Bonacich Measures as Equilibria in Network Models - Hannu Salonen (Aboa Centre for Economics (ACE), 2015)
We investigate the cases when the Bonacich measures of strongly connected directed bipartite networks can be interpreted as a Nash equilibrium of a non-cooperative game. One such case is a two-person game such that the utility functions are bilinear, the matrices of these bilinear forms represent the network, and strategies have norm at most one. Another example is a two-person game with quadratic utility functions. A third example is an m + n person game with quadratic utilitity functions, where the matrices representing the network have dimension m n. For connected directed bipartite networks we show that the Bonacich measures are unique and give a recursion formula for the computation of the measures. The Bonacich measures of such networks can be interpreted as a subgame perfect equilibrium path of an extensive form game with almost perfect information.
Keywords: C71; D85; 330; networks; influence measures; Nash equilibrium